Echocardiographic assessment of single‐ventricle diastolic function and its correlation to short‐term outcomes after the Fontan operation. (24th June 2019) - Davis, Erin K.; Ginde, Salil; Stelter, Jessica; Frommelt, Peter; Hill, Garick D.
Abstract: Background/Hypothesis/Objectives: Postoperative complications after the Fontan operation for single ventricle heart disease are common and include persistent pleural drainage and prolonged length of hospital stay (LOS). Diastolic ventricular dysfunction may increase risk for postoperative complications by raising central venous pressures. We sought to determine the relationship between preoperative echocardiographic measurements of diastolic function, including myocardial deformation imaging, on (a) preoperative invasive catheterization measurements and (b) postoperative outcomes after the Fontan procedure. Design/Methods: All patients that underwent Fontan procedure from 2011 to 2017 were included. Echocardiograms performed within 6 months prior to Fontan operation were evaluated. Measurements of ventricular global and diastolic strain and strain rate were performed offline with TomTec speckle tracking software. Other diastolic function measurements included atrioventricular valve inflow and annular tissue Doppler imaging. Diastolic function measurements were correlated with pre‐Fontan catheterization measurements and postoperative Fontan outcomes using Spearman's rho. Multivariable logistic regression for a prolonged LOS (>75%ile for postoperative LOS) was performed to adjust for preoperative risk factors. Results: A total of 141 patients were included in the study. Majority had single morphologic right ventricle (58.9%). Median age at time of Fontan was 3.4 years (IQR 2.9‐4). Median hospital LOS was 9 days (IQR 7‐11). Circumferential diastolic strain rate weakly correlated with LOS (rho = −0.21, P = .01). There was no correlation between any other diastolic strain measurements and pre‐Fontan end‐diastolic pressure or postoperative LOS. In multivariable analysis, E/E′ was the only echo measurement that predicted prolonged hospital LOS (OR 1.4, 95%CI: 1.1‐1.8, P = .003). Conclusion: Preoperative diastolic strain measurements did not have a strong association with postoperative Fontan outcomes. Increased E/E′ ratio, however, did predict greater LOS after Fontan procedure, and may be useful in preoperative risk stratification. Future studies are needed to further assess the utility of diastolic strain imaging in the single‐ventricle population.